HEDONISM IN FITZGERALD THE GREAT GATSBY - Raisa Murni Ananda.M; Burhanuddin Arafah (Journal of Innovation Research and Knowledge, 2023)
This research aimed to describe hedonistic characters in everyday life. The novel studied was entitled The Great Gatsby. Writer focused on the impact of hedonism based on Jay Gatsby’s character in this fictional novel. In this study, the writer used genetic structuralism approach, a literary research method that includes instrinsic and extrinsic aspects. Instrinsic aspect contained the elements of characters, plot, settings, and the themes analysis. The extrinsic aspect described as an outsideelements of the intirnsic aspect. In this literary work, life and lifestyle was truly depicted in the jazz era. This research data were analyzed using qualitative research method and described descriptively. The study found that the hedonistic lifestyle carried out by the Jay Gatsby in the novel has impacts towards losing identitiy, being betrayed by someone he loves and death.